2021
DOI: 10.2308/jiar-2021-104
|View full text |Cite
|
Sign up to set email alerts
|

International Accounting and Auditing Standards Adoption in Non-EU Eastern European Countries: Review of Regulations and Literature

Abstract: In this paper, we review the regulations and research on the adoption of international accounting and audit standards in eleven Eastern European countries outside of the European Union. We find many regulatory commonalities among these jurisdictions related to their Communist-bloc heritage. The state remains the most important stakeholder and tax accounting dominates financial reporting. The work of local auditors is considered less reliable than that of their Big 4 counterparts. International organizations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…The finding is consistent with numerous other studies that have confirmed that foreign corporations and international accounting firms have a substantial influence upon regulators and governments in the shaping of regulatory frameworks so that they represent the interests of the firms; see the work of (Chand and White 2007;Bhatia and Makkar 2019;Abdullatif and Al-Rahahleh 2020;Rykaczewski et al 2022). As Humphrey et al (2009) argued, major international accounting firms can potentially become involved in and responsible for setting global auditing standards.…”
Section: Foreign Corporations and The International Accounting Firmssupporting
confidence: 89%
“…The finding is consistent with numerous other studies that have confirmed that foreign corporations and international accounting firms have a substantial influence upon regulators and governments in the shaping of regulatory frameworks so that they represent the interests of the firms; see the work of (Chand and White 2007;Bhatia and Makkar 2019;Abdullatif and Al-Rahahleh 2020;Rykaczewski et al 2022). As Humphrey et al (2009) argued, major international accounting firms can potentially become involved in and responsible for setting global auditing standards.…”
Section: Foreign Corporations and The International Accounting Firmssupporting
confidence: 89%